2014
DOI: 10.1016/j.addr.2014.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The need for complex 3D culture models to unravel novel pathways and identify accurate biomarkers in breast cancer

Abstract: The recent cataloging of the genomic aberrations in breast cancer has revealed the diversity and complexity of the disease at the genetic level. To unravel the functional consequences of specific repertoires of mutations and copy number changes on signaling pathways in breast cancer, it is crucial to develop model systems that truly recapitulate the disease. Here we discuss the three-dimensional culture models currently being used or recently developed for the study of normal mammary epithelial cells and breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
252
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(257 citation statements)
references
References 141 publications
(158 reference statements)
5
252
0
Order By: Relevance
“…3D human-cell models may also provide more effective and economical screening of new drugs than the use of animal models. 8,9 Furthermore, in vitro 3D modeling of native tissue provides tools for regenerative medicine. However, understanding the fundamental cell biology is critical in translating in vitro discoveries into clinical applications, e.g., functional replacement of damaged tissue.…”
Section: Introductionmentioning
confidence: 99%
“…3D human-cell models may also provide more effective and economical screening of new drugs than the use of animal models. 8,9 Furthermore, in vitro 3D modeling of native tissue provides tools for regenerative medicine. However, understanding the fundamental cell biology is critical in translating in vitro discoveries into clinical applications, e.g., functional replacement of damaged tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, preclinical and patient data have suggested that PIK3CA mutations mediate resistance to therapies that target receptors in the ErbB family, specifically HER2 and EGFR (23,24,26,28). Increasing evidence has also implicated autocrine/paracrine signaling in drug resistance (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…To determine how constitutively activating mutations in PIK3CA affect responsiveness to HRG, we used a three-dimensional (3D), in vitro culture system in which cells form multicellular spheroids on micro-patterned culture plates, previously suggested to bridge the gap between monolayer and in vivo systems (28). We have found that cellular responses to growth factors are generally more pronounced when cells are grown in 3D culture than when grown in two-dimensional monolayers (unpublished observations).…”
Section: Pi3k Wt and Mutant Cells Exhibit Variable Responsiveness To Hrgmentioning
confidence: 99%
“…A series of excellent reviews have recently described in depth the use of 3D tissue culture model systems in pathophysiology [49] and high-throughput drug candidate toxicity analysis, [50] to identify tumor-specific signaling pathways and biomarkers, [51] and to determine growth determinants for drug target discovery. [52] These reviews delineate what parameters contribute to a disease representing, efficient [53] and dye [102]…”
Section: Current In Vitro Model Systems To Address Functions Of Metasmentioning
confidence: 99%